The Assistance Of Accounting Implementation Of Zakat, Infaq, And Operational Funds Based On Financial Reporting And Accounting Standard (PSAK) 109 In The Preparations Of Financial Statements Of National Zakat Agency (BAZNAS) In Pekalongan City - Yohani, Yohani; Moegiri, Moegiri; Hidayah, Rini; Yusuf, Muhamad (Prosiding University Research Colloquium, 2022)
The National Zakat Agency (BAZNAS) Pekalongan located in Jl. Majapahit No. 8 was formed based on the Decree of the Mayor of Pekalongan Number: 451.1/392 of 2016. It has some activities such as carrying out the collection, distribution and utilization of public funds in the form of zakat, and infaq/sadaqah in a professional and transparent manner. Therefore, it is necessary to be audited by a Public Accounting Firm (KAP) as a form of accountability for financial statements to muzaki. As we know, these funds accepted by civil service staff (ASN) of Pekalongan City, deducted by the payroll clerks. This Zakat received in the last 2 years amounted to Rp. 1,041,466,564 (2019) and Rp. 1,396,230,670 (2020), while the Infaq received was Rp. 633,654,150 (2019) and Rp. 687,103,358 (2020). These funds are distributed to mustahik in the form of basic necessities for the poor, orphanages, underprivileged children, honorary employees, Koran teachers, ibn sabil, and amil. Besides, these ones are also stored in the form of deposits and the profit sharing is used as operational funds. Every year the partners (the managers of Pekalongan BAZNAS) routinely make reports in the form of receipts and distributions (tasaruf) of these funds. However, the partners do not yet have or make consolidated financial reports between zakat, infaq, and operational funds in accordance with applicable accounting standards, namely PSAK 109. So that community service activities are needed in the form of assistance in the implementation of zakat accounting based on the standard in the preparation of the financial statements of this agency. So, with the assistance, the Financial Statements of BAZNAS can be audited by a Public Accounting Firm with a Fair Opinion.